2015
DOI: 10.1073/pnas.1503784112
|View full text |Cite
|
Sign up to set email alerts
|

Human population dynamics in Europe over the Last Glacial Maximum

Abstract: The severe cooling and the expansion of the ice sheets during the Last Glacial Maximum (LGM), 27,000-19,000 y ago (27-19 ky ago) had a major impact on plant and animal populations, including humans. Changes in human population size and range have affected our genetic evolution, and recent modeling efforts have reaffirmed the importance of population dynamics in cultural and linguistic evolution, as well. However, in the absence of historical records, estimating past population levels has remained difficult. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(122 citation statements)
references
References 93 publications
5
109
0
3
Order By: Relevance
“…The growth rate calculated from these data are significant because the methodology used to estimate the population size is completely independent from our analysis and therefore provides an important cross-check on the systematic uncertainties of the SPD approach. Many studies have indicated that SPDs are valid demographic proxies (25)(26)(27)(28)(29)(30)33). Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The growth rate calculated from these data are significant because the methodology used to estimate the population size is completely independent from our analysis and therefore provides an important cross-check on the systematic uncertainties of the SPD approach. Many studies have indicated that SPDs are valid demographic proxies (25)(26)(27)(28)(29)(30)33). Fig.…”
Section: Significancementioning
confidence: 99%
“…Radiocarbon dates provide a direct record of prehistoric human activity, and large samples have been used for quantitative demographic analysis (25)(26)(27)(28)(29)(30). Larger populations produce more datable material; thus, the temporal frequency of the radiocarbon record reflects the size of the population.…”
mentioning
confidence: 99%
“…Following Tallavaara et al (2015), the carrying capacity of Lower Austrian environments during the Upper Paleolithic would have varied between 0.1 and 4 inhabitants/100 km 2 , while Wobst (1974) has shown that, in the Paleolithic, the minimum number of persons required to form a viable reproductive network (the Bmaximum band^) is 175. In Lower Austria, any such network would therefore range across a territory of between 4375 and 175,000 km 2 .…”
Section: Can An Aurignacian Point Of Origin Be Found?mentioning
confidence: 99%
“…Surovell et al [5] proposed a means of addressing this bias through a process termed 'taphonomic correction', in which abundance is measured as actual abundance in the archaeological (or fossil) record for a particular time period relative to the abundance of geologic deposits of the same age. Since being proposed, taphonomic correction has proved an effective tool for better understanding dynamics of human and faunal abundance in the distant past [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%